Variación de perfiles genéticos obtenidos por PCR con y sin extracción de ADN a partir de manchas de sangre (2017)
ABSTRACT: The PCR without extraction is a key tool in forensic investigation, being a good option when samples with small amounts or degraded DNA are available. The objective of this study was to compare genetic profiles obtained by PCR using: i) DNA samples extracted using Chelex® 100, ii) DNA samples extracted using an FTA purification reagent, and iii) samples without extraction using the commercial kits AmpFLSTR® Identifiler®, routinely employed in the laboratory IdentiGEN of the University of Antioquia. Blood stains were collected in FTA cards Genecard WhatmanTM, chromatography paper, and in filter papers. PCR without extraction was performed using the buffers EzwayTM, PCRboostTM, STRboostTM, and Buffer 5X Colorless Go Taq® Flexi. The pro les were obtained by capillary electrophoresis. The results show that, using the above-mentioned buffers, all STR markers were amplified, for samples collected in the three different types of support. In conclusion, the PCR without extraction, apart from reducing the cost and time needed for processing the samples, it allows obtaining genetic pro les that meet the quality criteria established by the laboratory, in a more efficiently way, since DNA extraction and purification steps are eliminated. Key words: DNA extraction, forensic genetics, PCR without extraction.